Faktor yang Mempengaruhi Preferensi Bermukim Penghuni Perumahan Formal Kota Surakarta Studi Kasus Kelurahan Mojosongo - Fachrul Fadilla; Galing Yudhana; Erma Fitria Rini (ARSITEKTURA, 2017)
Surakarta city is a big city that has a tendency to relatively rapid growth rate. One of the examples in Mojosongo Village planned as new settlements in Surakarta city. The state settled in Mojosongo Village increased by 2, 65% and the total population increased by 24, 8% with the data collected in 2010 until 2013, so for the requirement of residential are still not fulfilled. Development planning of residential area is an alternative to solve the requirement of residents in Mojosongo Village.  Mojosongo Village as new settlements must prioritize the requirement of home that is appropriate for the residents of residential. The problems in this research is the dominant factor influencing preferences of residents of the formal housing in Mojosongo Village. The purpose of this research is to know the preferences settled for residents of residential in Mojosongo Village, Also what are the factors that influence it. In this research used deductive approach because this research was conducted by examining the theories derived from the literature using the selected variables that have been determined by the type of research combined with quantitative descriptive. The influence of each variable were then divided into the dependent variable and independent variables with analytical methods such as multiple linear regression and correlation test to look at the contribution of each factor has been reduced. The influence of each variable were then divided into the dependent variable and independent variables with analytical methods such as multiple linear regression and correlation test to know the contribution of each factor has been reduced. Based on the analysis, it is found that the dominant factor affecting preferences of settled residents in residential is water services. This research recommendations in the planning area is to development residentials area in accordance with the factors influencing. Keywords: Preference Settled, Residential, Surakarta